Optimasi Jaringan Hotspot Mikrotik Melalui Pendekatan Siklus Pengembangan Jaringan (NDLC) Di Kampus ITB Ahmad Dahlan - Aliyudin, Muhammad; Gumelar, Tommy; Arman, Shevti Arbekti (ITB Ahmad Dahlan Jakarta, 2022)
The advancement and rapid spread of the internet poses a challenge to provide more optimal network quality at the Ahmad Dahlan Institute of Technology and Business educational institutions (ITB-AD). To help manage the existing network, the campus uses a proxy as the main manager of the existing hotspot network. The problem experienced is that the hotspot login display still uses the default default from Mikrotik, blocking has not been applied to accessing adult content, the efficiency of available bandwidth has not been properly distributed, and there is no scheduled access to existing network users. The aim of this research is to optimize the quality of the ITB-AD hotspot network. To help solve problems that exist in research, researchers use the Network Development Life Cycle (NDLC) as a methodology in research. The results of this study are able to provide additional custom configurations for hotspot login displays, application of adult content blocking, burst bandwidth as bandwidth efficiency and implement access schedules for users in the hotspot network. The conclusion of the study is that using the NDLC method can optimize the quality of the ITB-AD hotspot network.